Model Pengembangan formula Rubber Membrane Filter Press - ., Nasruddin (Balai Riset dan Standardisasi Industri Palembang, 2013)
This reseach aimed to find the formula for rubber membrane filter press as substitution of imported ones.The treatment were kaolin (45, 50, 53, and coconut shell charcoal as a filler. The results showed that rubber membrane filter press-M3 had better chemical and physical properties than imported rubber membrane filter press. Test results for the rubber membrane filter press-M3 showed hardness value 126 shore A; tensile strength 173 kg/cm2 ; tensile strength of 200% with a value of 51 kg/cm2; elongation at break of 869%, tear resistance 119 kg/cm2 ; gravity of 1.992 g/cm2 and abrasion resistance DIN 210.6 mm2. The test results of rubber membrane filter press (M3) shows the development of the formula, kaolin derived from Bangka Island and coconut shell charcoal is added as a filler in rubber formula membrane filter press to improve the physical properties and gives a tendency to increase the bond between the rubber membrane-forming molecules filter press.Keywords: charcoal, kaolin, membrane, natural rubber, synthetic rubberÂ AbstrakTelah dilakukan karakterisasi rubber membrane filter press yang berasal dari impor sebagai dasar untuk pengembangan formula baru rubber membrane filter press dengan filler kaolin, arang tempurung kelapa. Hasil pengujian sifat mekanik dari beberapa formula pengembangan diperoleh data untuk formula rubber membrane filter press-M3 hasil ujinya lebih baik dari rubber membrane filter press impor. Rubber membrane filter press-M3 berdasarkan hasil uji untuk kekerasan 126 shore A; tegangan putus 173 kg/cm2; kuat tarik 200% nilainya 51 kg/cm2; perpanjangan putus 869%; ketahanan sobek 119 kg/cm2; berat jenis 1,992 g/cm2 dan ketahanan kikis DIN 210,6 mm2. Rubber membrane filter press (M3) dari formula pengembangan menunjukkan, kaolin dan arang tempurung kelapa yang ditambahkan sebagai bahan pengisi dapat meningkatkan sifat mekanik dan dapat meningkatkan ikatan antar molekul pembentuk rubber membrane filter press.Kata kunci : arang, membrane, kaolin, karet alam, karet sintetis